Longitudinal associations between sport participation and fat mass with body posture in children: A 5-year follow-up from the Czech ELSPAC study - Kasović, Mario; Štefan, Lovro; Piler, Pavel; Zvonar, Martin (PloS one, 2022)
The main purpose of the study was to examine longitudinal associations between sport participation and fat mass with body posture in children. We used data from children recruited in the Czech European Longitudinal Study of Pregnancy and Childhood (CELSPAC) at the ages of 11 y (n = 1065), 13 y (n = 811) and 15 y (n = 974). Information on body posture, practicing sport in a club and at a competitive level, and skinfold thicknesses (biceps, triceps, subscapula, suprailiaca and thigh) from pediatrician's medical records were collected. Body posture was inspected by a pediatrician. The sum of 5 skinfolds was used as a proxy of fat mass. The 85th and 95th percentiles defined 'overfat' and 'obese'children. Practicing sport in a club and at a competitive level were included as 'yes/no' answers. General linear mixed models with risk ratios (RR) and 95% confidence intervals (95% CI) were calculated. Overall, 35.6% of children and adolescents had impaired body posture; the prevalence of 'incorrect' body posture increased by age (from 41.0% to 28.0%, p<0.001). Practicing sport in a club and at a competitive level decreased by follow-up (p<0.001), while the level of 'overfat' and 'obese' children increased (p<0.01). In separate models, 'incorrect' body posture was associated with non-practicing sport in clubs (RR = 1.68; 95% CI 1.43-1.97, p<0.001) or at competitive level (RR = 1.61; 95% CI 1.37-1.88, p<0.001) and with being 'overfat' (RR = 2.05; 95% CI 1.52-2.75, p<0.001) and 'obese' (RR = 2.15; 95% CI 1.68-2.75, p<0.001). When all variables were put simultaneously into the model additionally adjusted for sex, self-rated health and baseline body posture, similar associations remained. This study shows, that not participating in sport and being overfat/obese are longitudinally associated with 'incorrect' body posture. Therefore, the detection of these risk factors in childhood, through the development of school- and community-based interventions, should be advocated.
Keywords: index tělesné hmotnosti; následné studie; obezita; postura těla; longitudinální studie; Follow-Up Studies; Posture; Longitudinal Studies; Humans; Obesity; Czech Republic; Adolescent; Child; Body Mass Index; dítě; lidé; mladiství; Česká republika